2016
DOI: 10.1016/j.msea.2016.08.119
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and deformation behavior of the hot-rolled medium manganese steels with varying aluminum-content

Abstract: We elucidate here the mechanistic contribution of the interplay between microstructural constituents and plastic deformation behavior in hot-rolled Fe-0.2C-11Mn-xAl steels containing 2-6 wt.% Al. The decrease in austenite fraction with increase in Al-content was accompanied by decrease in tensile strength, while the δ-ferrite content and ductility increased. 2Al steel was characterized by ultrahigh ultimate tensile strength (UTS) of 1407 MPa, while 6Al steel exhibited extremely high total elongation (TE) of 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 33 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…In addition, γ(α )+α layers show a higher capacity for crack arrest in cold-rolled 3Si samples. However, δ-ferrite was considered a soft phase in medium Mn steels [20,21], which contradicts the result of Sun et al Zhang et al [26] revealed that the propagation of cracks was slightly deflected when the cracks met the soft δ-ferrite phase. On the basis of these results, the influence of δ-ferrite resulting from the interaction of Si and Al on fracture behavior is not yet clear.Strain rate dependent TRIP effects, mechanical properties, and fracture behavior are vital factors during car crashes.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…In addition, γ(α )+α layers show a higher capacity for crack arrest in cold-rolled 3Si samples. However, δ-ferrite was considered a soft phase in medium Mn steels [20,21], which contradicts the result of Sun et al Zhang et al [26] revealed that the propagation of cracks was slightly deflected when the cracks met the soft δ-ferrite phase. On the basis of these results, the influence of δ-ferrite resulting from the interaction of Si and Al on fracture behavior is not yet clear.Strain rate dependent TRIP effects, mechanical properties, and fracture behavior are vital factors during car crashes.…”
mentioning
confidence: 90%
“…It is known that C and Mn can stabilize austenite, whereas Al and Si can stabilize ferrite [17]. Apparently, the formation of δ-ferrite is promoted as the Al/Si content increases [19,20]. Sun et al [19] revealed that 3 wt.% Si added to 0.2C-10Mn-3Al-(0-3)Si steel resulted in a large fraction of δ-ferrite, while there was no δ-ferrite at the addition of 1 wt.% Si.…”
Section: Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…7 Apart from that, the addition of Al also lowers density of this steel. 3 Si decreases the SFE and decreases the possibility of carbide precipitation. 8 It has been observed 7,8 that the conventional TWIP steel has Mn content in the range of 20–30 wt%, Al content nearly about 3 wt%, and Si content lies between 2 and 3 wt% with low carbon content to get desirable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%